Respuesta agronómica de dos variedades de maíz suave a tres tipos de labranza y fertilización nitrogenada en la comunidad Quisacoto, cantón San Miguel de Bolívar - Sánchez Vásquez, Milton Gonzalo (2022)
The corn is one of the consumer products listed and most necessary nutritional characteristics. The Bolívar province is the largest producer of soft corn in Ecuador with an area of 38 000 has. This research was conducted in the community Quisacoto of San Miguel canton, province Bolívar. The objectives were: i) validate the effect of three types of tillage on corn. ii) Evaluate the agronomic of two varieties of soft corn: INIAP 111 and common Guagal. iii) Determine the effect of three doses of nitrogen on yield and iv) Perform economic analysis of partial budget and the marginal rate of return. A complete block design applied randomly: factorial in plot divided with three replications. Factor A corresponded to three types of tillage and they were the main plots. The combination of factors B (two varieties of corn) and C (three doses of N) corresponded to the subplots. The main components of the performance and content of N in the soil before and at the end of the test were evaluated. Analysis of variance, Tukey, correlation, linear regression, polynomial trends and economic analysis was performed. There were different effect types of tillage, varieties and doses of nitrogen on yield. At higher doses of N (kg / ha), most was both corn and dry performance. Are measured dependent interactions among the factors being the most efficient tillage reduced the local variety Guagal and with 40 to 80 kg / ha of N. Finally, this research allowed to validate sustainable technological alternatives for mitigating climate change.